IMPLEMENTASI FUZZY LOGIC PADA SISTEM INFORMASI GEOGRAFIS PEMETAAN SEKOLAH BERBASIS WEB - Eva Siti Nurjanah (Prodi Sistem Informasi FST Universitas Jambi, 2025)
The Sukabumi District Education Office is currently crowding schools, but school management has not been able to be carried out optimally so this can lead to problems in education management. The Sukabumi district education office has a website as an information medium that can be accessed globally, however the information related to this website is general in nature, unable to describe in detail the state of a school. As in remote areas, a strategic plan is needed. Through this strategic planning, the Sukabumi District Education Office can systematically develop an effective and efficient managerial system, namely a web-based potential geographic information system for all schools. With the support of web-based GIS technology, users are expected to be able to access via the internet, so that the distribution of information can extend to the entire archipelago. The research used the data interview method by means of observation, literature study, and interviews. After the data is collected, analysis of system requirements and system design is carried out which includes system design, database design, menu structure design and interface design. Furthermore, the implementation of the system uses the LeafletJs javascript framework by taking the coordinating point (LatLong) using Google Maps for the author's programming language using the PHP based Codeigniter Framework and fuzzy as the algorithm used. After the application is generated, a program test is carried out with the Alpha Test.